2008
DOI: 10.1177/0960327107082231
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative EEG in occupational chronic solvent encephalopathy

Abstract: The aim of this study was to characterize the quantitative analyzed EEG (electroencephalogram) findings (qEEG) in chronic solvent encephalopathy (CSE) patients and study whether the qEEG findings associate with the duration and intensity of the solvent exposure. Also, the diagnostic value of qEEG in CSE is discussed. The EEG of 47 male CSE patients was analyzed. The laboratory’s own reference EEG values of 24 healthy male subjects formed the laboratory control group. We also used an age-matched contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In our study we did not find any significant relation between qEEG measuresand MoCA scores in manganese exposed workers.Protective measures of worker health may have reduced the effect of manganese exposure and thus manganese might not to be at a level to affect cognition. Another possibility is that MoCA scores of the patients included in the study were slightly affected, a study in patients with lower MoCA scores may reveal different outcomesKeski-Säntti et al did not recommend the use of qEEG in the clinical diagnostics of solvent encephalopathy because of the small amount and unspecificity of the observed abnormalities (33). Chronic occupational toxic exposure may not lead to significant findings in qEEG measures even if they cause cognitive deficits.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we did not find any significant relation between qEEG measuresand MoCA scores in manganese exposed workers.Protective measures of worker health may have reduced the effect of manganese exposure and thus manganese might not to be at a level to affect cognition. Another possibility is that MoCA scores of the patients included in the study were slightly affected, a study in patients with lower MoCA scores may reveal different outcomesKeski-Säntti et al did not recommend the use of qEEG in the clinical diagnostics of solvent encephalopathy because of the small amount and unspecificity of the observed abnormalities (33). Chronic occupational toxic exposure may not lead to significant findings in qEEG measures even if they cause cognitive deficits.…”
Section: Discussionmentioning
confidence: 99%
“…33 Likewise, exposure to solvent-based toxins can also influence the EEG. 34 The presence of heavy metals or illicit drugs, undetected and untreated, may impair clinical effectiveness because they affect neuronal interactions. Neurofeedback treatment of crack cocaine users showed better abstinence rates than without neurofeedback, but not as high as with alcoholics and opiate addicts using the Peniston-Kulkowsky protocol.…”
Section: Drugs Toxins Hormonesmentioning
confidence: 99%
“…Previously, some studies reported the effect of different chemicals on the brain function using EEG. The frontal theta power band is increased in the chronic solvent encephalopathy patient group when compared with the laboratory control group (Keski-Säntti, Kovala, Holm, Hyvärinen, & Sainio, 2008). Significant increases of dominant alpha frequency and alpha percentage were observed during the early phase exposure of m-xylene (Seppalainen et al, 1991).…”
mentioning
confidence: 98%